Assembling Science Dichotomy of Islamic and West Epistemology Perspective - Miftahudin Azmi; Nur Syam (JURNAL AT-TURAS, 2021)
The dichotomy of science has been going on for a long time, resulting in knowledge originating from Islamic civilization and Western civilization. This dichotomy ultimately requires scientific integration in various scientific disciplines and educational institutions. Whereas the source of all knowledge comes from God. The purpose of this article is to find a meeting point for the epistemology of Islamic scholarship (al-Qur'an) and the West so that in the end there is no dichotomy of knowledge. This research is normative because it examines the texts of Islamic and Western civilizations to find a meeting point for the scientific epistemology developed by the two civilizations. The results showed that the development pattern of scientific epistemology in the West tended to be dominated by reason and sensory experience (rationalism and empiricism). however, the last few periods of scientific epistemology in the West have developed intuitive methods that ultimately minimize or at least not mainstream the roles of reason and sense experience. This concept is similar to the Islamic epistemology system which carries reason (burhani), senses (bayani), and heart ('irfani).